(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
modular teaching dictates the reading of problematic and difficult lectures that provide generalized information on the major issues of science. Lectures should focus on developing students ’ creative abilities. The practical and laboratory classes of the module are formed together with the lectures, which supplement the content of the lectures with a new material from which they will be studied. Students will have practical skills.